2003
DOI: 10.1186/ar615
|View full text |Cite
|
Sign up to set email alerts
|

Differential recovery of glycosaminoglycan after IL-1-induced degradation of bovine articular cartilage depends on degree of degradation

Abstract: Arthritic diseases are characterized by a progressive loss of extracellular matrix (ECM), which may ultimately lead to frank tissue loss and gross joint damage. The conditions under which chondrocytes can be induced to replenish or repair a depleted matrix (and thereby prevent or slow the disease process) remain unclear. If these conditions were known, then in principal one could design a therapeutic strategy that takes into account the capacity (or absence thereof) for chondrocytes to repair their matrix natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 28 publications
3
3
0
Order By: Relevance
“…The result of possible partial recovery suggests that inhibition of cytokine activity or rapid cytokine clearance from the culture medium/joint space could suppress production of proteolytic enzymes and rescue PG synthesis via reduced cell death (see Eq (1) and Eq (S14) in S4 Text ). Similar PG recovery has been reported in experimental studies [ 74 , 75 ]. Specifically, our numerical model predicted PG recovery between days 10 and 30 ( Fig 8E , purple line) after removal of most IL-1 from the culture medium (day 10 in Fig 8A , purple line).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The result of possible partial recovery suggests that inhibition of cytokine activity or rapid cytokine clearance from the culture medium/joint space could suppress production of proteolytic enzymes and rescue PG synthesis via reduced cell death (see Eq (1) and Eq (S14) in S4 Text ). Similar PG recovery has been reported in experimental studies [ 74 , 75 ]. Specifically, our numerical model predicted PG recovery between days 10 and 30 ( Fig 8E , purple line) after removal of most IL-1 from the culture medium (day 10 in Fig 8A , purple line).…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, our numerical model predicted PG recovery between days 10 and 30 ( Fig 8E , purple line) after removal of most IL-1 from the culture medium (day 10 in Fig 8A , purple line). During a similar time-window as shown by our model, previous in vitro experiments showed partial recovery of uninjured bovine cartilage GAG content over 3 weeks after changing the medium to that without IL-1 [ 75 ]. Interestingly, less recovery was observed in the most severely degraded regions compared to the more intact regions of the cartilage after IL-1 treatment.…”
Section: Discussionsupporting
confidence: 66%
“…Long-term In vitro studies have been conducted which enabled monitoring changes of GAG distribution over time with high resolution, allowing insight into the process of cartilage degradation, development, and repair (42). For example, in a study by Allen et al bovine cartilage plugs were monitored over time and showed chondrocytes could replenish GAG after trypsin depletion of GAG (118) and after interleukin-1 (IL-1) treatment (119). GAG measurements have been observed to correlate better in superficial layers of cartilage as compared with deep layers where MRI can overestimate GAG (120).…”
Section: Contrast Enhanced Imaging - Delayed Gadolinium-enhanced Mri mentioning
confidence: 99%
“…This regulation is the result of interactions between ionic interstitial fluid and negatively charged sulfated glycosaminoglycans (sGAGs) attached to the PG backbone (2). The amount and distribution of PGs changes substantially during development (3), during degeneration and repair (4,5), and in response to blunt trauma (6). Of particular clinical interest, initial stages of OA are marked by aggrecanasemediated cleavage of PGs (7), resulting in altered sulfation patterns (8) and progressive depletion of PGs from the ECM.…”
mentioning
confidence: 99%